Perancangan Media Pembelajaran Dasar Desain Grafis Menggunakan Teknologi Augmented Reality - Muhammad Siddiq Al Hafizh; Vivianti Vivianti (Sekawan Institut, 2024)
Learning basic graphic design materials at SMK Negeri 1 Godean is carried out with less conducive classroom conditions because the media used in learning is not appropriate so that students are not motivated to learn and there are some abstract materials that are difficult for students to understand. This research aims to design a learning media for basic graphic design materials using augmented reality technology. The method used in this research is the development method or research and development with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The tools used in this research are Corel Draw X7, Blender 3D, Unity, Vuforia, and Visual Studio Code. The data analysis technique used in this research is quantitative descriptive analysis technique. This research produces a learning media for graphic design materials using augmented reality technology applied to SMK Negeri 1 Godean with the results of feasibility testing, namely the media expert test obtained a score of 92% which was classified in the very feasible category, the material expert test obtained a score of 80% which was classified as feasible, and the small group test obtained a score of 81.52% which was classified as very feasible. The effectiveness test obtained an N-Gain value of 0.8005 with a high category, the percentage value of increasing learning outcomes obtained a value of 80% with a moderate category, and the effectiveness value obtained a value of 80 with an effective category. Thus, it can be concluded that learning media for basic graphic design materials using augmented reality technology is feasible and effective for use in learning so that learning basic graphic design materials at SMK Negeri 1 Godean runs more effectively and can improve student learning outcomes.